1998
DOI: 10.1161/01.hyp.31.3.866
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin I 2 Contributes to the Vasodepressor Effect of Baicalein in Hypertensive Rats

Abstract: Abstract-Lipoxygenase inhibitors reduce blood pressure in hypertensive rats. The vasodepressor effect of lipoxygenase inhibitors may be related to increased production of prostaglandin (PG) I 2 since lipoxygenase-derived fatty acid hydroperoxides inhibit PGI 2 synthase. This hypothesis was examined in rats made hypertensive by infusion of angiotensin II (200 ng/min IP) for 12 to 14 days. In hypertensive but not in normotensive rats, the lipoxygenase inhibitor baicalein (60 mg/kg SC) increased (PϽ.05) the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In addition, the vasodepressor effect of baicalin has been previously reported in rats (Takizawa et al, 1998). The results of this study revealed that baicalin is more potent in renin inhibition than ACE inhibition, similar to the activity of sodium houttuyfonate analogs (Yuan et al, 2006), suggesting that baicalin, formerly an antimicrobial and antiviral agent, may interfere the RAS in vivo through renin and ACE inhibitions.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the vasodepressor effect of baicalin has been previously reported in rats (Takizawa et al, 1998). The results of this study revealed that baicalin is more potent in renin inhibition than ACE inhibition, similar to the activity of sodium houttuyfonate analogs (Yuan et al, 2006), suggesting that baicalin, formerly an antimicrobial and antiviral agent, may interfere the RAS in vivo through renin and ACE inhibitions.…”
Section: Discussionsupporting
confidence: 68%
“…In this protocol, the responses to NOR3 (30 g ⅐ kg Ϫ1 ⅐ min Ϫ1 iv) determined before and after treatment with indomethacin (5 mg/kg iv), SC-560 (5 mg/kg iv), NS-398 (5 mg/kg ip), or nimesulide (1 mg/kg iv) were compared. The doses of COX inhibitors were chosen on the basis of previous reports (1,7,31).…”
Section: Protocol 2: Effects Of Cox Inhibitors (Indomethacin Sc-560mentioning
confidence: 99%
“…Antiinflammatory, anti-HIV, anti-cancer, and anti-oxidant activities have all been reported for baicalein in in vitro studies using cell lines (reviewed in Lai et al, 2003). In vivo studies in rats have indicated that this agent also possesses anti-inflammatory and vasodepressor effects (Lin and Shieh, 1996;Takizawa et al, 1998).…”
Section: Introductionmentioning
confidence: 98%